Penerapan Model Pembelajaran Peer-Led Team Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Larutan Elektrolit Dan Nonelektrolit - Avni Dalemeng; Abdon Saiya (Oxygenius Journal Of Chemistry Education, 2021)
This study aims to improve student chemistry learning outcomes by applying the peer-led team learning model. This research design uses Classroom Action Research (CAR) which is divided into two cycles. With four stages, namely planning, action, observation and reflection. This research was carried out at SMA Negeri 1 Tagulandang in class X Science 1, totaling 31 students. This research is only focused on the material of electrolyte and nonelectrolyte solutions. In this study using instruments such as observation sheets, test questions and questionnaires. From the research that has been carried out, it is found that 77.41% of students have successfully met the Minimum Completeness Criteria (KKM) which was continued in the second cycle and obtained an average score of 77.58. From the results of student questionnaires and the results of observations given to students through peer-led team learning, students responded well. This shows that the peer-led team learning model has a positive impact on the learning process.